1999
DOI: 10.3171/foc.1999.7.5.10
|View full text |Cite
|
Sign up to set email alerts
|

The importance of shunt valve position in flow characteristics of the Medtronic PS Medical Delta valve

Abstract: This study was conducted to document the extent to which flow depends on valve position in relation to head-pressure reference. Medtronic PS Medical Delta valves (contour model, performance levels 0.5, 1.0, 1.5, and 2.0) were studied in a bench test designed to evaluate flow rates with respect to valve position in relation to the head-pressure reference postion. The valves were connected to an “infinite” reservoir by the standard inlet catheter. An initial head (proximal) pressure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…When normal CSF flows through the reservoir, the high SV concentration in the reservoir is continuously diluted. [9,10] In contrast, when the VP shunt malfunctions, the SV in the reservoir cannot be quickly diluted.…”
Section: Discussionmentioning
confidence: 99%
“…When normal CSF flows through the reservoir, the high SV concentration in the reservoir is continuously diluted. [9,10] In contrast, when the VP shunt malfunctions, the SV in the reservoir cannot be quickly diluted.…”
Section: Discussionmentioning
confidence: 99%
“…These variables were employed in unsupervised machine learning analysis to optimize the number and range of valve performance levels. It should be noted that shunt valve performance levels were also converted to drainage pressure values according to the respective manufacturer’s catalogs when specific drainage pressures were not recorded in the operative reports ( Francel et al, 1999 ; Chong et al, 2002 ; Lollis et al, 2010 ; Czosnyka et al, 2013 ; Mirone et al, 2019 ; Skalický et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, this study exclusively focused on infant hydrocephalus patients who demonstrated improvement after their first shunt surgery, with no documented shunt failures. This focus was based on our assumption (Francel et al, 1999;Chong et al, 2002;Lollis et al, 2010;Czosnyka et al, 2013;Mirone et al, 2019;Skalický et al, 2022) 5-2.5; 3.5-5.5; 7.0-9.0; 10.5-12.5; 13.5-15.5 1; 2; 2; 2; 2 1.00…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we said, we only recruited patients with improved outcomes and without valve adjustments over 7 months after shunt surgery. Hence, we defined an outlet pressure instead of the shunt, as reported in the Medtronic shunt catalog 40 . After applying the abovementioned processes, we calculated the ICP using FSI simulation for all 14 patients before shunt surgery and 7 stages after shunt surgery (Fig.…”
Section: Methodsmentioning
confidence: 99%